A Literature Review: Factors of Success and Failure of Accounting Information System Implementation - Sarsiti, Sarsiti (Devotion : Journal of Research and Community Service, 2019)
Organizations in the digital era increasingly understand the importance of implementing accounting information systems (AIS) because can help improve the efficiency and effectiveness of business processes, as well as assist managerial decision making. In reality, not all AIS implementations are successful, because information systems are not just computerized systems that are run manually but more than that involve business processes and resource utilization. This article is a literature review aimed at understanding the factors that determine the success and failure of implementing an accounting information system. The discussion was carried out descriptively based on a literature review and previous findings related to the determining factors for the success and failure of implementing an accounting information system.